PENDUGAAN PARAMETER DEMOGRAFI DAN MODEL PERTUMBUHAN MONYET EKOR PANJANG (Macaca fascicularis) DI PULAU PEUCANG, TAMAN NASIONAL UJUNG KULON - Budi Sampurna; Yanto Santosa; U Mamat Rahmat (Media Konservasi, 2014)
Long tailed macaqueis one of the prospective species in international trade and still facing seriously threatened due to high demand for exporting purposes.The research was aimed at the estimation of demographic parameter and  population growth model.The inventory was conducted using sensus method by concentration point Analyses were conducted on demography parameter (size and density, sex ratio,natality and mortality),  and population growth model estimation. The result showed that long-tailed macaque in Peucang island, Ujung Kulon National Park (UKNP) had total population size 82 individuals, was found in 4 groups of Macaca. Population size in general was between 9 – 42 individuals/group. The age structure of the populazioln was  progressive population  with global sex ratio of 1 : 1,2. The life-span of long tailed macaque  is beetween 0,6-0,86 depend on age structure and the general fecundity figures throughout this locationis 0.23. Fecundity ratein this research was obtained by dividing the number of individuals existing infants and compared with the individual number of productive females. The growth model of long-tailed macaquein Peucang Island was growth model adrift age. Keywords : Demographic parameter,Growth Model, Long-tailed macaque, Spatial distribution,Ujung Kulon National Park (UKNP).